Designing 3D Animation about Breaststroke Swimming Technique Using MDLC Method - Jensen Tanedy; Surya Tjahyadi; Tony Wibowo (Universitas Internasional Batam, 2024)
Drowning is serious, yet neglected health issue. Drowning is a leading cause of death for children and young people. The risk of drowning can be caused by many factors, one of them inability to swim. Swimming is a sports that exercise most parts of our body. Beside as a sport, swimming can also be a life saver. With this problem, author want to increase knowledge to prevent the risk of drowning by designing a 3D animation about breaststroke swimming technique. The design of animation uses Blender 3.6 and Adobe Premiere Pro software. Multimedia Development Life Cycle (MDLC) method was used on design process with interview to collect data. The result of this study is a 02:02 minutes 3D animation which is distributed using Youtube platform.